Question #3ecb0

1 Answer
Oct 3, 2017

We can prove this using mathematical induction.
The answer got too lengthy and there will be some improvement.

Explanation:

[Part 1] Base case(#n=2#)
To show that the recurrence is true for #n=2# we have to evaluate #L_1#, #L_2#, #K_1# and #K_2#.

#K_1=L_1=3# is obvious, as there are only three string: #(0) (1) (2)#.

#K_2=6# because the 2-words string from the set #{0,1,2}# in which the two maximum blocks have single word are
#(0,1) (0,2) (1,0) (1,2) (2,0) (2,1)#.

#L_2=7#, as all strings without adjacent 0 and 2 are
#(0,0),(0,1),(1,0),(1,1),(1,2),(2,1),(2,2)#

Thus, #L_2=K_2+1/3K_1# is true.

[Part 2]
What we need to do is to find a recurrence for #K_n# #(n>=3)# .

This part is long, so I posted it in another article.
https://socratic.org/questions/what-is-the-recurrence-formula-for-k-n-k-n-is-the-number-of-strings-a-1-a-2-a-n-

The result is #K_1=3, K_2=6, K_n=2K_(n-1)+K_(n-2)" "(n>=3)#

[Part3] Then we are going to find the recurrence of #L_n# #(n>=3)# .
Again, I posted it in another article.
https://socratic.org/questions/what-is-the-recurrence-formula-for-l-n-l-n-is-the-number-of-strings-a-1-a-2-a-n--2
The result is #L_1=3, L_2=7, L_(n+1)=2L_n+L_(n-1)" "(n>=2)#

[Part 4] This is the main section of mathematical induction. (#n=k->n=k+1#)

Suppose that #L_k=K_k+1/3K_(k-1)# is true for a certain #k>=2#.
Using the recurrences in Part 2 and Part 3:
#L_(k+1)=2L_k+L_(k-1)#
#=2(K_k+1/3K_(k-1))+(K_(k-1)+1/3K_(k-2))#
#=2K_k+5/3K_(k-1)+1/3K_(k-2)#

#K_(k+1)+1/3K_k=(2K_n+K_(n-1))+1/3(2K_(n-1)+K_(n-2))#
#=2K_k+5/3K_(k-1)+1/3K_(k-2)#

We reached #L_(k+1)=K_(k+1)+1/3K_(k)# at last!

[Part 1] and [Part 4] ensure that the proof is completed.